2020
DOI: 10.1088/1742-6596/1440/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

Profile of critical thinking skills in student’s SMPN 1 Kalipare at topic of substance and its characteristics

Abstract: One of the 21st century skills that students must possess is critical thinking skills. This research aims to determine critical thinking skills of students at SMPN 1 Kalipare topic of substances and its characteristics. This type of research is quantitative descriptive research. The research was conducted at SMPN 1 Kalipare. The research sample were 83 students of class VIII in 2018/2019 academic year and were assigned random sampling. The instrument used was 15 multiple choice test questions of critical think… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
1
5
0
2
Order By: Relevance
“…Kemampuan berpikir kritis yang merupakan salah satu indikator keterampilan abad-21 menjadi sorotan dunia dan sangat diperlukan dalam kehidupan (Amin, Duran Corebima, Zubaidah, & Mahanal, 2017;Nisa, Nafiah, & Wilujeng, 2020;Puspita, Kaniawati, & Suwarma, 2017). Demirhan & Köklükaya (2014) mengatakan bahwa penting setiap warga Negara untuk mengembangkan kebiasaan mandiri dan berpikir kritis.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Kemampuan berpikir kritis yang merupakan salah satu indikator keterampilan abad-21 menjadi sorotan dunia dan sangat diperlukan dalam kehidupan (Amin, Duran Corebima, Zubaidah, & Mahanal, 2017;Nisa, Nafiah, & Wilujeng, 2020;Puspita, Kaniawati, & Suwarma, 2017). Demirhan & Köklükaya (2014) mengatakan bahwa penting setiap warga Negara untuk mengembangkan kebiasaan mandiri dan berpikir kritis.…”
Section: Pendahuluanunclassified
“…Menurut Juhji & Suardi (2018), seorang guru harus memiliki kemampuan kritis, jiwa kreatif, dan komitmen yang tinggi untuk mengembangkan intelegensi dan kemampuan berpikir kritis siswa. Permasalahan di Indonesia bahwa kemampuan berpikir kritis siswa masih lemah (Amin et al, 2017;Arafah et al, 2021;Nisa et al, 2020;Puspita et al, 2017), sehingga kondisi yang berkaitan dengan berpikir kritis perlu menjadi sorotan dalam studi penelitian yang tidak hanya ditinjau dari perspektif siswa tetapi juga dari tingkat kemampuan berpikir kritis guru. Menurut Bezanilla et al (2019) adanya hubungan antara kerangka cara pandang kemampuan berpikir kritis guru dengan pengembangan kemampuan berpikir kritis siswa.…”
Section: Pendahuluanunclassified
“…It can be trained to the students through learning [49] while increasing students' curiosity so that students seek information and formulate solutions to the facing of problems [50]. Teachers need to adjust appropriate learning in order to develop students' critical thinking skills [10].…”
Section: Development Of Sts Ipa Learning Tools Integrated Local Potential Of Kacang Shanghai To Increase Critical Thinking Skills and Tecmentioning
confidence: 99%
“…The result of PISA in the field of science in 2018 showed that Indonesian students obtained a score of 396 by an average score of 489 [9]. The cause of students' lack of critical thinking skills is to learn which is emphasizing critical thinking skills where it has not become the main focus of learning in schools [10]. The learning process has certainly implemented activities to inquire questions, provide solutions, and solve problems that can raise students' critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this critical thinking skills are very important to become students because they are sone of the skills that are central to the future development of the world community (Redhana, 2013) and are important for someone to have to enter the industrial world as it is today (Nuryanti, Masykuri, & Susilowati, 2018). However, many studies in the field of education in Indonesia show that students' critical thinking skills are still relatively low (Bhakti et al, 2019;Mahbubah, Habibulloh, Hermita, & Samsudin, 2020;Ningsih et al, 2019;Nisa, Nafiah, & Wilujeng, 2020).…”
Section: ▪ Introductionmentioning
confidence: 99%